The Setback of Indonesia Democracy in The Covid-19 Pandemic Era in Law-Making Process - Firdaus, Fahmi Ramadhan (Universitas Widya Gama Malang, 2025)
At the beginning of 2020, the world was faced with the COVID-19 Pandemic which had an impact on various fields, from health, economics, education to politics and law, especially in the Law-Making Process, the existence of Large-Scale Social Restriction policies to overcome the Pandemic on the other hand had an impact on limited space for participation. The public takes part in the Law-Making Process due to the policy to reduce meetings involving large crowds in one place, apart from that the issue of transparency worsens the practice of the Law-Making Process during the Covid-19 Pandemic, including the revision of the Mineral and Coal Law and the Law-Making Process of the Job Creation Law, even though the existence of the law is the basis for the government to act and carry out its functions is an essential thing in a civil law based state. A good law must fulfill 2 (two) aspects, including the material and the formal aspects. Several practices that deviate from formal aspects of the Law-Making Process during the Covid-19 Pandemic violate the principles of participation and transparency and threaten democracy. Through a normative juridical approach with conceptual, statutory and comparative approaches, this research aims to explain the symptoms of legislative practices that threaten democracy during the Covid-19 Pandemic. The research results show that participation in the Law-Making Process during the Pandemic was weak and not transparent. In the future, as an effort to maximize public participation in the Law-Making Process during the emergency period, it needs to be supported by the adoption of information technology to comprehensively support the public's role in the Law-Making Process at every stage, coupled with the Constitutional Court Decision No. 91/PUU-XVIII/2020 which orders meaningful public participation in Law-Making Process.